The Land Question: Exploring Obstacles to Land Redistribution in South Africa - Lungisile Ntsebeza (After Apartheid, 2011)
The gradual conversion of a large number of the indigenous people of presentday South Africa into wage laborers, particularly after the discovery of minerals in the latter part of the nineteenth century (see Bundy 1988; Mafeje 1988), has led to a peculiar situation in which the land question in South Africa has been marginalized. Yet, compared with the situation in other countries on the African continent, the extent of land plunder in South Africa was extraordinary. The Natives Land Act of 1913 was the first major legislative attempt on the part of colonialists to grab a substantial amount of the